2014
DOI: 10.2217/nnm.13.26
|View full text |Cite
|
Sign up to set email alerts
|

Development and In Vitro Evaluation of Slippery Nanoparticles for Enhanced Diffusion Through Native Mucus

Abstract: Taking enhanced mucus-penetrating properties into account, neutral nanoparticles were shown to be very promising in drug delivery via mucus membranes of different cavities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 26 publications
2
50
0
2
Order By: Relevance
“…2). Since it has been reported that near-neutral potentials 14 and PEG modification could effectively reduce the interaction of 9 particles with mucus and enhance the particle stability, these results further demonstrated that the distinctive mucus-penetrating property resulted solely from the difference in shape.…”
mentioning
confidence: 65%
“…2). Since it has been reported that near-neutral potentials 14 and PEG modification could effectively reduce the interaction of 9 particles with mucus and enhance the particle stability, these results further demonstrated that the distinctive mucus-penetrating property resulted solely from the difference in shape.…”
mentioning
confidence: 65%
“…Positive charge caused adhesion to mucus fibers, while negative-charged NPs were repelled by the anionic barrier, and hydrophobic interactions can prevent permeation of uncharged particles (Aljayyoussi et al 2012). Transport data of polyacrylic acid/polyallylamine copolymers (neutral), polyacrylic acid (negative charge) and polyallylamine (positive charge) NPs through porcine mucus showed that neutral NPs can cross the mucus layer better than charged ones (Laffleur et al 2013).…”
Section: Mucus Layermentioning
confidence: 99%
“…Furthermore, Laffleur et al could demonstrate with this system that 'slippery' neutral nanoparticles prepared via ionic interaction between the anionic polymer poly(acrylic) acid and the cationic polymer poly(allylamine) exhibited a high diffusion efficiency [30]. The neutral nanoparticles were compared with poly(allylamine) nanoparticles and poly(acrylic acid) nanoparticles prepared by ionic gelation with tripolyphosphate and calcium ions, respectively.…”
Section: Transwell-snapwell Systemmentioning
confidence: 99%